ETOS SOSIAL MASYARAKAT BELITUNG DALAM NOVEL SIRKUS POHON KARYA ANDREA HIRATA ( KAJIAN SOSIOLOGI SASTRA ) - Wahida, Dinda Nahdlotul; Yanuarsih, Sri; Letreng, I Wayan (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Social ethos of society is the integrity of the most influential values on a particular people, especially in human behavior. The purpose of this study is to obtain detailed knowledge about the negative aspects in social form, based on the realities in Indonesian society, which can be presented and described through the three aspects of social ethos based on Max Scheler's theory: (1) poverty, (2) ignorance, and (3) ineffectual education. The subject of this study is the novel "Sirkus Pohon" by Andrea Hirata, which contains many relevant realities with this study that will be conducted. Descriptive Qualitative method which is the data consisting of factual information and utilizing a sociological literary approach. The data collection technique involves documentation by selecting literary works as objects, followed by analysis through reading, marking sections, taking notes, literature review, grouping data into a corpus, analyzing, and drawing conclusions. The findings indicated that poverty was influenced by the inability to get basic needs due to high unemployment rates within certain group of society. Consequently, ignorance arose as a result of economic problems, leading to the inability to afford education, which became the primary cause. In the end, ineffectual education occurred due to the narrow-mindedness of individuals, arguing that the outcome of education did not guarantee a decent livelihood and this mindset became the impact of the weakness in the economy and education field that they were facing.